Antioxidant and anti-inflammatory activities of lycopene against 5-fluorouracil-induced cytotoxicity in Caco2 cells - Norah M. Alhoshani; Mohammed Al-Zharani; Bader Almutairi; Nada H. Aljarba; Norah S. AL-Johani; Nora Alkeraishan; Abdullah A. AlKahtane; Saud Alarifi; Daoud Ali; Saad Alkahtani (Elsevier, 2022)
5-fluorouracil (5FU) is widely used to treat colorectal cancer (CC) and its main mechanisms of anticancer action are through generation of ROS which often result in inflammation. Here, we test the effect of Lycopene against 5FU in Caco2 cell line. Caco2 cells were exposed to 3 µg/ml of 5FU alone or with 60, 90, 120 µg/ml of lycopene. This was followed by assessment of cytotoxicity, oxidative stress, and gene expression of inflammatory genes. Our findings showed that Lycopene and 5FU co-exposure induced dose-dependent cytotoxic effect without compromising the membrane integrity based on the LDH assay. Lycopene also significantly enhanced 5FU-induced SOD activity and GSH level compared to control for all mixture concentrations (p < 0.01). Lycopene alone and combination with 5FU-induced expression of IL-1β, TNF-α, and IL-6. Furthermore, IFN-γ expression was significantly enhanced by only mixture of lycopene (90 µg/ml) and 5FU (p < 0.05). In conclusion, Lycopene supplementation with 5FU therapy resulted in improvement in antioxidant parameters such as catalase and GSH levels giving the cell capacity to cope with 5FU-mediated oxidative stress. Lycopene also enhanced IFN-γ expression in the presence of 5FU, which may activate antitumor effects further enhancing the cancer killing effect of 5FU.